Formation of insulin amyloid fibrils followed by FTIR simultaneously with CD and electron microscopy. - Bouchard, M; Zurdo, J; Nettleton, E; Dobson, C; Robinson, C (2000)
Fourier transform infrared spectroscopy (FTIR), circular dichroism (CD), and electron microscopy (EM) have been used simultaneously to follow the temperature-induced formation of amyloid fibrils by bovine insulin at acidic pH. The FTIR and CD data confirm that, before heating, insulin molecules in solution at pH 2.3 have a predominantly native-like alpha-helical structure. On heating to 70 degrees C, partial unfolding occurs and results initially in aggregates that are shown by CD and FT-IR spectra to retain a predominantly helical structure. Following this step, changes in the CD and FTIR spectra occur that are indicative of the extensive conversion of the molecular conformation from alpha-helical to beta-sheet structure. At later stages, EM shows the development of fibrils with well-defined repetitive morphologies including structures with a periodic helical twist of approximately 450 A. The results indicate that formation of fibrils by insulin requires substantial unfolding of the native protein, and that the most highly ordered structures result from a slow evolution of the morphology of the initially formed fibrillar species.